Post-mortem magnetic resonance (PMMR) imaging of fetal central nervous system: A systematic review. (December 2017) - Filograna, L.; Bernardi, B.; Flach, P.M.; Martinez, R.M.; Carducci, C.; Thali, M.J.; Tomà, P.
Abstract: In this systematic review the diagnostic capabilities of post-mortem MR (PMMR) concerning brain and spinal cord abnormalities compared to traditional autopsy were analyzed. A computerized online search of scientific articles was performed using Medline (PubMed) databases in June 2016 to identify all studies comparing PMMR with conventional autopsy in detecting fetal central nervous system alterations. Titles and abstracts were screened based on these exclusion criteria: no paediatric cases, neuroradiological alterations not reported, studies not in English, case reports and reviews, less than 10 subjects analyzed, PMMR performed on MR Units with magnetic field different from 1, 5 or 3 T. Full texts of potentially relevant publications were read. Only articles with a clearly stated comparison between PMMR and autopsy results were included. 467 abstracts were identified; 14 papers met the inclusion criteria; data from 8 studies were extracted (467 cases). Of the 8 papers examined all regarded fetuses; only one analyzed also children <16 years. The percentages of concordance for pathology and general concordance between the two techniques were equal or superior to 90% in 7/8 and over 90% in 5/8 studies, respectively. In 5/7 works where the rating of false positives (FP) and false negatives (FN) was possible, FP numbers were superior to FN ones: in 72/467 cases (15%) PMMR suggested pathologies not confirmed by autopsy, in 27/467 cases (6%) autopsy showed alterations not detected by PMMR. Based on these results, PMMR might be considered a valid support/substitute to traditional autopsy for studying fetal central nervous system. Highlights: Modern imaging techniques are used as substitutive tools to autopsy, especially in the pediatrics. It is necessary to augment knowledge in PMMR imaging of fetal central nervous system. PMMR shows potentials in providing information about central nervous tissue in fetuses. PMMR can be a valid support to autopsy for the study of brain and spinal cord alterations. It could be a screening method for successive autopsy, or a confirmatory method for ante-natal diagnoses.